2020
DOI: 10.1080/15623599.2020.1819584
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric review of the status and emerging research trends in construction safety management technologies

Abstract: Technologies such as virtual reality (VR), online databases, Geographic Information Systems (GIS), Building Information Modelling (BIM), Unmanned Aerial Vehicle (UAV), 4 D Computer-Aided Design (4 D CAD), wearable robotics have been adopted to improve construction site health and safety. However, little attempt has been made to map global research on construction health and safety technologies. Therefore, this paper conducts a review of technologies for construction health and safety management to reveal emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 85 publications
3
85
0
2
Order By: Relevance
“…As an epistemological stance, interpretivism was adopted in order to critically review extant literature and generate questions that then informed the ensuing inductive research approach, which sought to generate new theory on "negotiation" as a viable procurement path [100]. Interpretivism has been extensively used within construction management and civil engineering research [101][102][103]. For example, Roberts et al [104] reviewed the benefits and challenges of digital asset management, while Al-Saeed et al [105] sought to automate construction manufacturing procedures using building information modelling (BIM) digital objects.…”
Section: Methodsmentioning
confidence: 99%
“…As an epistemological stance, interpretivism was adopted in order to critically review extant literature and generate questions that then informed the ensuing inductive research approach, which sought to generate new theory on "negotiation" as a viable procurement path [100]. Interpretivism has been extensively used within construction management and civil engineering research [101][102][103]. For example, Roberts et al [104] reviewed the benefits and challenges of digital asset management, while Al-Saeed et al [105] sought to automate construction manufacturing procedures using building information modelling (BIM) digital objects.…”
Section: Methodsmentioning
confidence: 99%
“…), and the link strength is denoted by the proximity between nodes [48]. VOSviewer has been utilised to a plethora of topics ranging from contemporary trends in construction management technology [55] to mega-event orchestration such as the Formula One grand prix [56]. Researchers specifically note the capability of the technique to analyse large datasets.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers specifically note the capability of the technique to analyse large datasets. Using VOSviewer, Akinlolu et al [55] were able to show, when analysing extant literature on construction health and safety, that Africa was substantially underrepresented in research and suggested this as an area for future research. Similarly, Chamberlain et al [56] were able to demonstrate that a lack of knowledge regarding mega-event managers has hindered researchers' ability to 'learn lessons' from previous mega-events.…”
Section: Methodsmentioning
confidence: 99%
“…All these applications are capable of creating and depicting basic bibliometric networks; however, VOSviewer was selected for our study due to the ease of use, easy interpretability of networks through visualization, and the popularity of the software in engineering and management research (Tariq et al 2020). Science mapping analysis has already been employed in different research areas, such as construction safety (Akinlolu et al 2020), megaprojects (Wang et al 2020), and acoustic-based leak localization (Hu et al 2021), which has yielded meaningful research outcomes including (1) working linkages and measurements between researchers, countries, and organizations and (2) preliminary ideas on the existing research themes and future research directions (Tariq et al 2020). In our study, VOSviewer was used for science mapping of journal sources, contributing countries, and popular keywords.…”
Section: Science Mapping Analysismentioning
confidence: 99%